2020
DOI: 10.1186/s40168-020-00863-4
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater viral metagenome reveals novel and functional phage-borne antibiotic resistance genes

Abstract: Background: Antibiotic resistance developed by bacteria is a significant threat to global health. Antibiotic resistance genes (ARGs) spread across different bacterial populations through multiple dissemination routes, including horizontal gene transfer mediated by bacteriophages. ARGs carried by bacteriophages are considered especially threatening due to their prolonged persistence in the environment, fast replication rates, and ability to infect diverse bacterial hosts. Several studies employing qPCR and vira… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 82 publications
10
98
1
Order By: Relevance
“…It is worth noting that the role of phages in spreading antibiotic resistance genes has been raised in a growing number of articles as well, which clearly reflects an increased interest in phage-based therapeutics in general [57][58][59][60]. Metagenomic studies have confirmed the presence of such genes in phages isolated from a vast range of environments, which is in line with their ability to transfer genetic material between hosts.…”
Section: Unfavorable Impact Of Phages On Aquatic Reservoirsmentioning
confidence: 93%
See 1 more Smart Citation
“…It is worth noting that the role of phages in spreading antibiotic resistance genes has been raised in a growing number of articles as well, which clearly reflects an increased interest in phage-based therapeutics in general [57][58][59][60]. Metagenomic studies have confirmed the presence of such genes in phages isolated from a vast range of environments, which is in line with their ability to transfer genetic material between hosts.…”
Section: Unfavorable Impact Of Phages On Aquatic Reservoirsmentioning
confidence: 93%
“…In fact, a recent study detected that environmental waters contain a large reservoir of resistance genes, conferring resistance to tetracyclines and β-lactamases. Those genes, detected in phage DNA, were isolated from freshwater, water treatment plants, and oceans [57,59]. Aquatic environments may promote dissemination and acquisition of antibiotic resistance genes [61], which should be taken into consideration in aquacultures.…”
Section: Unfavorable Impact Of Phages On Aquatic Reservoirsmentioning
confidence: 99%
“…The virome data can also be used to predict putative host-phage systems by matching virome sequences to the CRISPR array sequences of bacterial CRISPR-Cas systems 7,8 or bacterial signature genes 9,10 . Virome sequences are also very useful for the discovery of novel phage genes, including antibiotic resistance genes, that are carried by uncultured phages 11,12 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Horizontal gene transfer (HGT) has regarded as the major pathway of ARGs transmission, which includes conjugation, transformation and transduction [9]. As a dominant pathway of HGT, conjugation is the transfer of ARGs through a pilin bridge between a donor and a recipient, which is usually achieved via mobile genetic elements (MGEs), such as plasmids (pMV158oriT), insertion sequences (IS613), integrons (intI-1), transposons (tnpA-03), and phages [10,11]. HGT can occur in any environment, especially where bacterial densities are high, such as in soil [12], in the gut microbiome of humans and animals [4]; and it has been shown to provide microbes with a wide variety of adaptive traits for microbial survival and proliferation under the pressure of antibiotics, heavy metals and other environmental contaminants [13].…”
Section: Introductionmentioning
confidence: 99%